Design, Automation and Test in Europe
DOI: 10.1109/date.2005.184
|View full text |Cite
|
Sign up to set email alerts
|

Instruction Scheduling for Dynamic Hardware Configurations

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Let us try to schedule the configuration prefetches for the three hardware modules on the given CFG. If we use the method developed by Panainte et al [PBV05], the result is shown in Figure 3.4b. As we can see, the load for M 3 can be propagated upwards in the CFG from node M 3 up to r. For nodes M 1 and M 2 it is not possible (according to this approach) to propagate their load calls to their ancestors, because they are in placement conflict.…”
Section: Motivational Examplementioning
confidence: 99%
See 2 more Smart Citations
“…Let us try to schedule the configuration prefetches for the three hardware modules on the given CFG. If we use the method developed by Panainte et al [PBV05], the result is shown in Figure 3.4b. As we can see, the load for M 3 can be propagated upwards in the CFG from node M 3 up to r. For nodes M 1 and M 2 it is not possible (according to this approach) to propagate their load calls to their ancestors, because they are in placement conflict.…”
Section: Motivational Examplementioning
confidence: 99%
“…To our knowledge, the works most closely related to our own, presented in Section 3.2, are [S + 10], [LH02] and [PBV05]. Panainte et al proposed both an intra-procedural [PBV05] and an inter-procedural [PBV06] static prefetch scheduling algorithm that minimizes the number of executed FPGA reconfigurations taking into account FPGA area placement conflicts.…”
Section: Static and Hybrid Configuration Prefetchingmentioning
confidence: 99%
See 1 more Smart Citation
“…II-A), makes the on-line approach feasible. The execution of M i is done in hardware or in software (lines [11][12][13][14], depending on the run-time conditions. Once the execution of M i finishes, we save its timestamp and then we compute the estimated performance gains G kMi (line 17) for all the modules currently recorded in the hardware history register HW (line 16).…”
Section: The Priority Function γ Mkmentioning
confidence: 99%
“…Many static algorithms for prefetching were proposed: [9], [12], [17], [10]. All share one limitation: in case of nonstationary behavior, they are unable to adapt, since the prefetch schedule is fixed based on average profiling information.…”
Section: Introduction and Related Workmentioning
confidence: 99%